Fast and Fresh Chicken Farm - Daip, Seliah; Lim, Lynda Azlina; Guido, Vianney; Danius, Gloria; Bauk, Sutia (2014)
Our business is focus to producing fresh chicken from the special chick whereby the chicken supply we got from our own farm which is we nurture before supply to the customer. Nowadays, the fresh chicken is having highly demand in the market. Moreover, the fresh chicken will used in several ways. The meat will use as food and the eggs will can use to do biscuits. On the contrary, the dirt of chicken can will use as fertilizers. For the first step is, our company will produce the fresh chicken which is we growth the chicken first and then, in mature age we will farm the chicken before it is delivery in the market. Besides that, high demands of fresh chickeh in the market has been enabled us to take the opportunity open this business. Indeed, the people also give this company chances to develop the company to more expand in this business. Identically, these industries also play an important role in order to challenge the Sabah development Corridor objectives. At the same time, the Sabah government also gives support to the private companies to modernize and develop the chicken fresh industry. Although this company is a new in this industry and lack of experiences but with the helps and encouragement from local government, we believe that this industry can give a benefit and high profit to our company and at the same time can develop the national economy. In a nutshell, the reason why we choose fresh chicken is because of the high demand from the people and this business have a many high profit in implement it. In facts, Malaysia is the best quality of chicken fresh production. Equally important, the most important things is fresh chicken also can be used in many ways and this business bring many benefit to our company.